Some hermeneutical assumptions latent within the gospel apparatus of Eusebius of Caesarea - O'Loughlin, Thomas (Peeters, 2017)
The presence of Eusebius’s gospel apparatus (often incorrectly referred to as ‘the Eusebian Canons’) in the margins of so many of gospel codices, both in Greek and over the whole range of versions, is sufficient evidence of the importance of that work in the history of gospels’ study. At first sight, it appears an unproblematic tool: it allows the reader to note at a glance whether a point being made in one gospel’s text (sometimes as long as one of our chapters and on other occasions less than a sentence) is to be found in all four, or just three or two gospels, or nowhere else; and then, if appropriate, to find those ‘parallels’. As such it is a gospel ‘harmony’ which preserves the integrity of each gospel, and of the four distinct gospels in that it avoids creating a fifth text, a diatessaron. However, built into the apparatus is a series of hermeneutical assumptions about how gospel texts relate to history, how the four texts relate to one another, how the four relate to ‘the gospel,’ how the texts were to be read together to provide a single composite history of Jesus, an apologetic before those who would point out their mutual discrepancies (e.g. Porphyry), and what constitutes ‘a parallel.’ Lastly, when we compare Eusebius’s assumptions with those used today (e.g. regarding ‘the Synoptic Problem’) we can observe the extent to which his method determined the overall shape of gospel comparison until the eighteenth century whereby there was a notional complete story of Jesus of which the four actual texts were specific redactions / perspectives.